2020
DOI: 10.3389/fonc.2020.00151
|View full text |Cite
|
Sign up to set email alerts
|

Gross Total vs. Subtotal Resection on Survival Outcomes in Elderly Patients With High-Grade Glioma: A Systematic Review and Meta-Analysis

Abstract: Background: The optimal strategy for the management of high-grade glioma in the elderly (≥60.0 years) remains controversial, especially regarding the effects of surgical extent on survival outcomes. The purpose of this study was to compare gross total resection (GTR) with subtotal resection (STR) for treatment effects in elderly patients with high-grade glioma.Methods: Three electronic databases were systematically searched, including PubMed, EmBase, and the Cochrane library, from inception to August 2018. Haz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 46 publications
(45 reference statements)
1
37
0
Order By: Relevance
“…In particular, the ≥65 years patient cohort had higher rates of both major and minor complications and prolonged LOS than those reported in prior studies, which used results showing lower rates of poor outcome compared to the present study to conclude that tumor resection in older patient populations is safe in carefully selected patients. [ 16 , 18 , 19 ] Our results reinforce the need for careful consideration and preoperative optimization of medical comorbidities and other risk factors more prevalent among older patients. [ 2 , 33 ] It is also notable that many of these prior studies were conducted on patients with glioblastoma alone.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In particular, the ≥65 years patient cohort had higher rates of both major and minor complications and prolonged LOS than those reported in prior studies, which used results showing lower rates of poor outcome compared to the present study to conclude that tumor resection in older patient populations is safe in carefully selected patients. [ 16 , 18 , 19 ] Our results reinforce the need for careful consideration and preoperative optimization of medical comorbidities and other risk factors more prevalent among older patients. [ 2 , 33 ] It is also notable that many of these prior studies were conducted on patients with glioblastoma alone.…”
Section: Discussionsupporting
confidence: 63%
“…[ 4 , 10 ] However, most studies suggest that intra-axial tumor resection in older patients is safe in well-selected patients. [ 16 , 18 , 19 ] Similarly, age has been correlated with poorer outcomes in meningiomas in the absence of careful consideration of preoperative medical risk factors that may disproportionally affect older patient populations. [ 6 , 9 , 11 , 13 , 21 , 23 , 29 ] Several case series have reported age as an important prognostic factor for infratentorial tumor outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The survival data were further analyzed using a Cox proportional-hazard model, adjusted for factors that were known to influence the outcome of GBM patients such as age, Karnofsky Performance Scale (KPS), therapy, extent of surgical resection, MGMT methylation and IDH mutation status [ 19 , 20 , 21 , 22 ]. The proportional hazard assumption testing for Tctex1 showed a p -value of 0.515, indicating that the assumption of this model was satisfied.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, STR is defined as removal of a portion of the tumor and residual tumor lesions are observed in post-operative images. Based on the systematic reviews and meta-analyses conducted by Brown et al and Han et al, studies showed that GTR significantly improves progression-free survival (PFS) and overall survival for GBM patients in comparison to STR [ 11 , 12 ]. However, multiple tumor lesions, bilateral tumor involvement, and bulky tumors pose a clinical challenge and risk for total resection [ 13 ].…”
Section: Current Treatment For Glioblastoma Multiforme (Gbm)— Where We Are Now?mentioning
confidence: 99%